2006
DOI: 10.1002/lt.20863
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of rat ischemic hepatic preconditioning after cold preservation identified by microarray analysis

Abstract: Hepatic ischemia-reperfusion injury associated with liver transplantation is an as yet unresolved problem in clinical practice. Preconditioning protects the liver against the deleterious effects of ischemia, although the mechanism underlying this preconditioning is still unclear. To profile gene expression patterns involved in hepatic ischemic preconditioning, we analyzed the changes in gene expression in rat livers by DNA microarray analysis. Approximately 116 genes were found to have altered gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…GDF15 expression has been linked to either anti- or pro-apoptotic function in several disease models. It is conceivable that GDF15 plays a pro-apoptotic protein role in cancer cells, whereas GDF15 acts as an anti-apoptotic protein in non-cancer cells [14, 33, 34]. The latter was described by Kempf and colleagues, who discovered GDF15 induction in the heart as a defense mechanism from warm I/R injury by reducing apoptosis in a coronary artery ligation model [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GDF15 expression has been linked to either anti- or pro-apoptotic function in several disease models. It is conceivable that GDF15 plays a pro-apoptotic protein role in cancer cells, whereas GDF15 acts as an anti-apoptotic protein in non-cancer cells [14, 33, 34]. The latter was described by Kempf and colleagues, who discovered GDF15 induction in the heart as a defense mechanism from warm I/R injury by reducing apoptosis in a coronary artery ligation model [13].…”
Section: Discussionmentioning
confidence: 99%
“…It is known to have pleiotropic functions involving stress response, inflammation, tumorigenesis, metastasis, angiogenesis, and tissue injury and recovery pathways [12]. It has been reported that GDF15 is upregulated in ischemic heart tissues in ae coronary artery ligation model [13], in rat liver tissues exposed to ischemic preconditioning before ischemia [14] and in the heart in response to hypertrophic conditions [15]. This quick up-regulation of GDF15 is aimed at preventing cells from further damage [13, 14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results provided evidence that miR-223 may be somehow involved in the process of hepatic I/R injury. Hepatic I/R injury is a complex physiological process that is associated with the interaction of many genes and proteins [10][11][12]25]. MiRNAs are known to be important mediators of gene regulation in response to cell-to-cell signaling and act in negative feedback of gene regulation [26].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that these events are partially medicated by alteration in molecular processes such as transcription and translation [10][11][12]. MicroRNAs (miRNAs) are a class of endogenously expressed small non-coding RNAs that are involved in regulation of translation and degradation of messenger RNA (mRNA) [13].…”
Section: Introductionmentioning
confidence: 99%